Hand hygiene practice in intensive care unit in port Harcourt, Nigeria - Mato, Christie N.; Ijah, Rex Friday Ogoronte A.; Alex-Wele, Mary A.; Uzosike, Tondor C.; Dayi, Joy O.; Hart, Fiekabo; Oruobu-Nwogu, Ayanate; Johnson, Uyoata Udo (International Surgery Journal, 2025)
Background: Modern healthcare practice recognizes the critical importance of handwashing / hand hygiene with recommendations made to that effect by the centre for disease control and the World Health Organization. This study evaluated the hand hygiene practices of staff users of the intensive care unit before and after patients’ care. Methods: A prospective analytical observational study was conducted in the first quarter of the year 2023, among health workers using mixed methods approach. Data was analysed using the Statistical Package for Social Sciences (SPSS) version 20.0. Results: Out of the 154 respondents who filled questionnaire, there were 72 (46.8%) males, 82 (53.2%) females and a mean age of 34.22±7.39 years. One hundred and thirty (84.4%) respondents were aware of the WHO five moments of hand hygiene. Ninety-six (62.3%) respondents opined that they practiced hand hygiene. However, observation revealed that 510 (98.5%) out of the 518 covertly observed participants did not carry out hand hygiene before patient care and 209 (40.3%) performed hand hygiene after patient care. The dominant reasons for non-compliance were lack of running water (n=126, 81.8%), absence of awareness posters (n=100, 64.9%) and absence of soap for hand washing (n=26, 16.9%). A statistically significant relationship was observed between the frequency of practice of hand hygiene and the category of staff. Conclusions: Less than expected hand hygiene practice was observed among members of staff, revealing need for emphasis and retraining of staff.